2023
DOI: 10.1186/s12933-023-01820-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting long-term prognosis after percutaneous coronary intervention in patients with new onset ST-elevation myocardial infarction: development and external validation of a nomogram model

Abstract: Background The triglyceride glucose (TyG) index is a well-established biomarker for insulin resistance (IR) that shows correlation with poor outcomes in patients with coronary artery disease. We aimed to integrate the TyG index with clinical data in a prediction nomogram for the long-term prognosis of new onset ST-elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (PCI) . Methods This retrospective study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In recent years, nomograms have been increasingly used to diagnose and predict a variety of diseases, including cancer ( Balachandran et al, 2015 ), myocardial infarction ( Ye et al, 2023 ), and hypertension ( Zhang et al, 2022 ). The utilization of nomograms serves to simplify the interpretation of pertinent risk factors, aiding both clinicians and patients in navigating the challenges posed by diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nomograms have been increasingly used to diagnose and predict a variety of diseases, including cancer ( Balachandran et al, 2015 ), myocardial infarction ( Ye et al, 2023 ), and hypertension ( Zhang et al, 2022 ). The utilization of nomograms serves to simplify the interpretation of pertinent risk factors, aiding both clinicians and patients in navigating the challenges posed by diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable nomograms can be of immense value in predicting the prognosis of eyelid tumors and other malignancies, assisting patients in decision-making, and aiding healthcare providers in personalizing clinical treatments. [30][31][32][33] The traditional AJCC classification system focuses on the tumor's largest diameter and invasion profile. However, our retrospective study showed that the degree of pathological differentiation, Ki67 expression, and pagetoid infiltration of the conjunctival epithelium could also increase the risk of recurrence, with specific predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked the clinical profile of ACS patients at admission to prognosis, with age, cardiac insufficiency, and blood pressure clinically recognized as independent markers of poor prognosis following PCI in ACS patients (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%